Study on constraint of mixed mode crack and failure assessment diagram of pressure-bearing structure - MIAO Xinting; LIU Guoxu; ZHANG Jinbo; PENG Jian; BIE Fengfeng (Jixie qiangdu)
The crack tip constraint and failure assessment diagram （FAD） in both plate specimen and pipe structure were studied to find out the compatibility and correlation of between the sample and piple.Based on the finite element method, constraints at crack tip of central cracked plate （CCP） specimen and cracked pressure pipe were obtained.It was found that crack tip constraint of CCP specimen under uniaxial loading is better matched with thick-walled pipeline under axial tensile loading, while CCP specimen under biaxial loading is better matched with thin-walled pipeline under internal pressure.In addition, the failure assessment diagram of CCP specimen and pipeline were obtained.It was found that FAD of CCP specimen is less related with thickness, when the thickness of pipe is within the range of thick wall or thin wall; was also pointed out that stress parallel to the crack direction increases the failure assessment curve （FAC） of the structure. Finally, it is found that FAC of the central crack plate specimen is higher than that of the pressure bearing pipeline, for the two structures with the same constraint level，and crack tip mixed mode degree and loading mode. That is, it is unsafe to use FAD of CCP specimen to evaluate pipeline.